Spatial and temporal acuity of visual perception can be enhanced selectively by attentional set. - Correa, A; Nobre, A (2008)
The aim of this research was to study the relationship between perceptual judgments about space and time. If spatial and temporal judgments were dissociable, they should be modulated selectively by attention. We compared the effect of the attentional set upon fine-grained spatial versus temporal discrimination of visual perception in two experiments. Using identical sensory stimulation, we measured perceptual judgments on either the size of a small spatial gap or the duration of a brief temporal gap. The attentional set was manipulated by cuing the task that was most likely to be performed. In one experiment, a neutral cue was also used, to measure relative benefits and costs of spatial and temporal task sets. If the attentional set could be directed selectively to spatial and temporal task-relevant dimensions, performance on both spatial and temporal acuity tasks should be specifically modulated by task cuing. The results showed that the attentional set enhanced the speed and accuracy of perceptual judgments similarly on both spatial and temporal tasks. Moreover, accuracy in one task was selectively enhanced by attending to that task while remaining unaffected by attending to the alternative task. This finding suggests multiple mechanisms, by which visual processing of spatial and temporal features can be selectively prepared without interfering with one another.